Decidual stromal cell therapy for generalized lymphadenopathy as a special clinical manifestation of COVID‐19 infection: A case report. Issue 5 (16th May 2022) - Pirsalehi, Ali; Soleimani, Masoud; Hajifathali, Abbas; Sadeghi, Behnam; Farhadihosseinabadi, Behrouz; Akhlaghi, Sedigheh Sadat; Roshandel, Elham
Abstract: We are going through the greatest global health crisis of the last decades, the coronavirus disease 2019 (COVID‐19) pandemic. It may cause morbidity and mortality in some cases, and there is no therapeutic approach with reproducible and favorable outcomes. As clinical manifestations differ from patient to patient, any report regarding clinical symptoms has been beneficial for early detection and treatment. Due to the immunomodulatory effect of mesenchymal stem cells (MSCs), MSCs‐based therapy has been approved to be one of the therapeutic strategies for COVID‐19 management. For the first time in the literature, we reported generalized lymphadenopathy with fever and no sign of respiratory distress in a 16‐year‐old patient with confirmed COVID‐19 infection as the main clinical signs. We also introduce decidual stromal cells as a potential immunomodulatory treatment for COVID‐19–infected patients. Abstract :